Recent Discoveries in Nanoparticle–Macrophage Interactions: In Vitro Models for Nanosafety Testing and Novel Nanomedical Approaches for Immunotherapy - Fernando Torres Andón (MDPI AG, 2021)
Nanoparticles (NPs) offer unique properties for biomedical applications, leading to new nanomedicines [...]